A. Tarskiego kryterium monotoniczności operatora konsekwencji w międzykulturowych badaniach systemów wniskowań - Sikora, Sławomir (Investigationes Linguisticae, 2016)
In this article I refer to the issue of comparative research methodology and methods of philosophical argumentation systems with different cultural areas. In relation to that shown by A. Tarski logical consequence operator, will establish criteria for the comparative analysis of systems inferences different cultural areas of the property based on the operator monotonic consequences.